YESEVİ KÜLLIYESİ BRONZ KAPI TOKMAKLARI: TİMURLU SANAT DÜNYASI AÇISINDAN BİR DEĞERLENDİRME - Başak Burcu TEKİN (Fırat University, 2019)
The Yasawi Shrine was built by Timur in 1397 to honour Khawaja Ahmad Yasawi 230 years after his death in Turkestan. Today when you visit the city of Turkestan (Yasi) in Kazakhstan, you can sense a feeling of eternity inspired by the gigantic building. The structure’s significance comes from the importance attributed to the Sufi Sheikh Khawaja Ahmad Yasawi. This building symbolises both the spiritual power of Yasawi and the worldly reign of Timur and the Eurasian steppes. The subject of this paper is the doorknockers on the entrance door of this shrine. The aim of this study is not only to examine the doorknockers but also to expose their place in Timurid art. Accordingly, the doorknockers will be analyzed from an artistic perspective, and the iconographic descriptions will illustrate how Timur understood symbolism in art. As an integrative and comparative study, this paper examines several sources of Timur’s political and art history, the iconography of Buddhism and Islam which were dominant in the region, Yasawi Sufi thought and Ahmad Yasawi’s poetry. Also included are comparisons of the miniatures, wooden artworks and architecture. This research shows Timur’s artistic powerful and far-reaching influence as it was reflected in the massive Ahmad Yasawi Shrine and in its smallest art works like the doorknockers.